Strega Nona takes a vacation - DePaola, Tomie, 1934-2020- (G.P. Putnam's Sons, 2000)
Strega Nona sends home gifts of candy and bubble bath while on vacation, but when Bambolona grabs the candy, Big Anthony is left with a lot of bubbles.